2011
DOI: 10.1111/j.1423-0410.2011.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and specificity of red‐blood‐cell antibodies in a multiethnic South and East Asian patient population and influence of using novel MUT+Mur+ kodecytes on its detection

Abstract: Antibodies to vMNS antigens are common in South and East Asian populations and are often missed when using standard screening cells. Use of specifically engineered screening cells to express red-cell antigens artificially is beneficial in detecting the diverse alloantibodies present in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Antibodies to GP.Mur red cells (probably mainly anti -Mur, but often called anti -' Mi a ' ) have been responsible for immediate and delayed HTRs [332,333] and severe HDFN [333 -335] (reviewed in [336] ). Antibodies to GP.Mur cells are among the most common atypical alloantibodies detected in eastern Asia [219,220,322,337,338] . They often have an IgM component; of those that contain IgG, it is almost always IgG1 and/or IgG3, and of those containing IgG, 69% were reactive in a monocyte monolayer functional assay [339] .…”
Section: Anti-mur and Other Antibodies To Gp Mur Red Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to GP.Mur red cells (probably mainly anti -Mur, but often called anti -' Mi a ' ) have been responsible for immediate and delayed HTRs [332,333] and severe HDFN [333 -335] (reviewed in [336] ). Antibodies to GP.Mur cells are among the most common atypical alloantibodies detected in eastern Asia [219,220,322,337,338] . They often have an IgM component; of those that contain IgG, it is almost always IgG1 and/or IgG3, and of those containing IgG, 69% were reactive in a monocyte monolayer functional assay [339] .…”
Section: Anti-mur and Other Antibodies To Gp Mur Red Cellsmentioning
confidence: 99%
“…The DRB1 * 0901 allele frequency was signifi cantly higher in patients with anti -' Mi a ' than in a control group [340] . Red cells resembling GP.Mur cells have been synthesised by embedding appropriate peptides attached to lipids in the membrane of red cells of common phenotype [337,341] . Red cells resembling GP.Mur cells have been synthesised by embedding appropriate peptides attached to lipids in the membrane of red cells of common phenotype [337,341] .…”
Section: Anti-mur and Other Antibodies To Gp Mur Red Cellsmentioning
confidence: 99%
“…Antibodies against these antigens are often the most commonly reported RBC antibodies among patient populations in Southeast and East Asia . The actual prevalence of these antibodies in affected Asian populations is not clear, however, in view of the lack of a uniform policy for antibody screening or usage of relevant reagent cells for their detection.…”
mentioning
confidence: 99%
“…The peptide sequence TYPAHTANE corresponds to Mur and SQTNDKHKRDT to MUT. Using these screening cells, we have previously shown that anti‐Mur and anti‐MUT can be separately identified . Anti‐Mi a is however not identified using these cells, as they have not been engineered to express the Mi a antigen.…”
mentioning
confidence: 99%
“…3. Initial developmental testing [8] and later field testing [51,52] over the last few years have established that MUT kodecytes will detect both anti-MUT and anti-Mi a while…”
Section: 'Miltenberger' Fsls and Kodecytesmentioning
confidence: 99%